CURRENT TRENDS IN TRANSLATION STUDIES: DIGITAL TECHNOLOGIES IN TRANSLATION PRACTICE AND RESEARCH (KONFERENSIYA, 2026)
The present paper will analyse modern tendencies in the study of translation with a special emphasis on the introduction of digital technologies in the translation practice and research. Particular focus is given to the change in the professional role of the translator in the context of the machine translation, the computer-based translation tools, and the use of corpus. The paper examines the impact of digital solutions on the quality of translation, the speed of translation, and methodological approaches in the modern field of translation research. The results demonstrate the increased necessity of interdisciplinary skills and critical analysis of technological solutions in translation studies.